Synthesis, characterization and performance of membranes for clarification of lemon juice - Chornomaz, Patricia Mariana (2011)
Two membranes named M1 and M2 from polysulfone (PSF) and polyvinylidenefluoride (PVDF), respectively, were prepared in our laboratory in order to determine their structural characteristics and to evaluate their efficiency in lemon juice clarification. Both membranes were characterized by scanning electron microscopy (SEM), liquid-liquid displacement, contact angle measurements, and the water permeability (Lh). Asymmetric membranes with a sponge-like and finger-like substructure for M1 and M2, respectively, were obtained. M1 PSF membrane had a smaller pore size and a higher porosity than PVDF but it had a higher value of permeate flux and lower fouling. The quality of clarified juice was evaluated in terms of: total soluble solids (TSS), suspended solids (TS), pH, citric acid content (% citric ac.). The resulting clarified lemon juice was highly similar to the initial juice but the reduction of the hesperidin (HSP) was lower for M2 (34%) when is compared to M1 (41%).